The Analysis of Validity and Reliability of the Indonesian’s SCARED Instrument Using the Rasch Model - Qadriyyah, Qadriyyah; Suprananto, Suprananto; Hayat, Bahrul (LPPM Universitas Negeri Jakarta, 2025)
This study aimed to evaluate the psychometric properties of the Indonesian version of the Screen for Child Anxiety Related Emotional Disorders (SCARED) using Rasch model analysis. The SCARED instrument was translated and adapted through a systematic process involving forward translation, backward translation, and expert reviews in both linguistics and psychology. A pilot study was conducted with 51 junior high school students to assess the instrument's validity and reliability. The Rasch analysis revealed satisfactory psychometric properties with a person reliability of 0.91 and item reliability of 0.94, indicating high consistency in measurement. The separation indices (person = 3.14, item = 4.00) demonstrated the instrument's ability to differentiate between varying levels of anxiety among respondents and varying item difficulties. The item information function analysis showed that most items had good discriminating power, particularly at moderate anxiety levels. These findings suggest that the Indonesian version of SCARED is a valid and reliable instrument for screening anxiety disorders in Indonesian children and adolescents. Further studies with larger and more diverse samples are recommended to establish normative data and confirm the five-factor structure of the instrument across different age groups and cultural contexts.